Thermal Modeling of Solar Still Coupled with Heat Pipes and Experimental Validation (Journal of Engineering, 2020)
Water is the basis of the existence of all kinds of life, so obtaining it with good quality represents a challenge to human existence and development especially in the desert and remote cities because these areas contain small populations and water purification requires great materials and huge amounts of fossil fuels resulting pollution of the environment. Cheap and environmentally friendly desalination methods have been done by using solar distillations. Passive solar stills have low yields, so in this research, the problem is overcome by connecting four heat pipes which are installed on the parabolic concentrator reflector with passive solar still to increase the temperature of hot water to more than 90°C, as a result, the yield increases. An extensive theory is studied to manufacture two systems: the first consists of passive solar still has dimensions are 1000 mm × 500 mm and the glass cover tilted at the angle 33°. It is approximately equal to the latitude of the city of Baghdad [(Latitude: (33.34° N) Longitude:  (44.4° E)].  This gives 5.04 kg/m2.day, the second solar still which is associated with 4 heat pipes gives a water yield of about 7. 2 kg/m2.day. This means that the improvement in the daily production of distilled water is 50 % over the productivity of the passive solar still All results above are calculated when the depth of water is 1. 5 cm. In addition, heat balance for each part of the system is achieved and calculations of the performance of the solar still are done by using the program in the language of Matlab. All these results are compared with the experimental ones of different depths of water (1.5 cm, 2 cm, 3 cm, and 4 cm) which are taken from the experimental part to ensure the system reliability at different weather conditions in Baghdad throughout the year and to give a good approach. The system associated with heat pipes gives promising results and can be widely used for its abundant productivity and durability of its components. (TDS) and (pH) value are carried out in the laboratory and it is found that water is safe and pure for drinking.